Making the difficult career transition: Writing the next chapter during the great resignation or in the future - Coppola, Paul J.; Young, Aprille F. (Frontiers in Psychology, 2022)
During the midst of the Great Resignation, over 4.5 million people have changed jobs. While a job change does not register as one of the top three drivers of stress, career transition-related stress does present itself as one of the top 25 causes. This stress can be reduced through social support models, career transition planning, and personal brand strategy frameworks. These adaptive change models become part of a continuous learning and growth process. This literature review aims to contribute to the industry and define career transition through a more holistic personal brand strategy utilizing a wide range of disciplines considering the challenges and opportunities presented during the Great Resignation.